An investigation of dielectric tunable materials for microwave tunable devices - Xiao, Li (2011)
Today, many of the communication systems are operated in several different bandwidths. Till now, the common solution to get a multi bandwidth transmitter/receiver is to insert several fixed microwave devices with different bandwidth to the required standard. This increases the size and power consumption of trans/receiver. One solution is to develop electronically tunable microwave devices. By replacing several fixed microwave devices with a single electronically tunable device, the size and power consumptions of the transmitter/receiver can be significantly reduced.